Analysis of Community Institution Empowerment as a Village Government Partner in the Participative Development Process - Nina Angelia; Beby Masitho Batubara; Rizkan Zulyadi; Taufik Wal Hidayat; Riri Rezeki Hariani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research focuses on analyzing the empowerment of social institutions as village government partners in the participatory development process. The location is in Percut Village, Percutseituan District, Deliserdang Regency. The background that is used as a reference for this research begins with the understanding that the urgency of villages in development in Indonesia is so urgent. The village is given authoritative to grow and develop in line with the development of its own community. Furthermore, the village holds millions of pieces of knowledge of the virtues of life and harmony of local wisdom that should be maintained, can be recognized from the mantra of three orders, namely; ordinances, manners, and manners (Zamroni, 2017). This kind of thinking construction is important to restate in order to examine the current relationship between the village government and the community (social institutions). Social institutions as partners of the Village Government have a very strategic role; start to formulate participatory development plans, implement, control, utilize, maintain and develop participatory development, mobilize and develop participation, mutual cooperation and community self-help, and foster dynamic development of the community in the context of community empowerment. Seeing the huge role that village community institutions have, it is important and interesting that this research is carried out to see the existence of community institutions as village government partners in the participatory development process. With this research, it will provide reference data for stakeholders related to community institution empowerment. In addition, it is an academic study in public policy and provides input to the village government regarding the reference to the model of community institution empowerment as a partner of the village government in order to work together to manage development in a participatory village. As for answering the problem of this study using qualitative methods and types of research with a descriptive approach. The targeted research output is a journal article and as a follow up will create a model in the institutionalization of village community organizations.